An Electron-bifurcating Caffeyl-CoA Reductase - Bertsch, Johannes (American Society for Biochemistry and Molecular Biology, 2013)
A low potential electron carrier ferredoxin (E(0)′ ≈ −500 mV) is used to fuel the only bioenergetic coupling site, a sodium-motive ferredoxin:NAD(+) oxidoreductase (Rnf) in the acetogenic bacterium Acetobacterium woodii. Because ferredoxin reduction with physiological electron donors is highly endergonic, it must be coupled to an exergonic reaction. One candidate is NADH-dependent caffeyl-CoA reduction. We have purified a complex from A. woodii that contains a caffeyl-CoA reductase and an electron transfer flavoprotein. The enzyme contains three subunits encoded by the carCDE genes and is predicted to have, in addition to FAD, two [4Fe-4S] clusters as cofactor, which is consistent with the experimental determination of 4 mol of FAD, 9 mol of iron, and 9 mol of acid-labile sulfur. The enzyme complex catalyzed caffeyl-CoA-dependent oxidation of reduced methyl viologen. With NADH as donor, it catalyzed caffeyl-CoA reduction, but this reaction was highly stimulated by the addition of ferredoxin. Spectroscopic analyses revealed that ferredoxin and caffeyl-CoA were reduced simultaneously, and a stoichiometry of 1.3:1 was determined. Apparently, the caffeyl-CoA reductase-Etf complex of A. woodii uses the novel mechanism of flavin-dependent electron bifurcation to drive the endergonic ferredoxin reduction with NADH as reductant by coupling it to the exergonic NADH-dependent reduction of caffeyl-CoA.